Happiness Management Model To Improve Performance In Organizations (Journal of Namibian Studies : History Politics Culture, 2023)
The university has experienced a decrease caused by dissatisfaction in the daily performance, in a situation of policies of scarce protection of the collaborators and without dialogue that aligns happiness as the main quality of human development and, therefore, of the organizations. The purpose of this research is to determine the correlation between happiness management and the performance of employees in the welfare area of the Universidad Nacional Pedro Ruíz Gallo; the sample of 40 employees assigned to the welfare area was selected as a census sample, and the results are theoretically justified since they will be an essential contribution to the administration. In addition to determining the relationship between the management of happiness and the performance of the collaborators, the relationship is analyzed between vision and strategic thinking, decision, quality orientation, coalition, process management, attitude and negotiation in the collaborators of the welfare area of the Universidad Nacional Pedro Ruiz Gallo. As a result, it was determined that there is a direct and significant relationship between the management of happiness and the performance of university welfare collaborators, which means that collaborators in happiness scenarios increase their performance